Study guides

Q: If a is 3 what is 2a plus 5 equal to?

Write your answer...

Submit

Related questions

2a-3+4b-2a-b-2a-b-3+5 Can be simplified to: 3b-1

2a-3+4b-2a-b-3+5=3b-1

(6a3 - 19a2 + 15a)/(2a - 3) = a(6a2 - 19a + 15)/(2a - 3) = a(2a - 3)(3a -5)/(2a -3) = a(3a - 5)

3b -1

9a +8 -2a -3 -5a = 2a +5

2a2 - 13a + 15 = (2a - 3) (a - 5)

If 3a+5=5a+3, then: 3a+5 - 3a = 5a+3 - 3a 5=2a+3 5 - 3=2a+3 - 3 2=2a a=1

3a + 4b - 5 - 1a + 7b + 3 - 1b 2a + 10b - 5 + 3 2a + 10b - 2

(a - 5)(a + 3) = a2 - 2a - 15

2a-5

2a+5a=3 7a=3 a=3/7 or .4286

2a+5

a+b+2+3=5+a+b

a=5

12(8a + 28) + 2a + 5 84a + 336 + 2a + 5 86a + 341

No. 2a is one thing, 3b is another. If you add them together, they become 2a + 3b. 5ab indicates that multiplication has taken place. 5 times a times b = 5ab

2a + 4b - 52a + 4b - 52a + 4b - 52a + 4b - 5

Start with simplifying: 2a + -3 = 5 and reordering: -3 + 2a = 5. Then add '3' to each side of the equation: -3 + 3 + 2a = 5 + 3 and you get 2a = 8 once all like terms are combined. The last step is to divide both sides by 2 and you get the answer, which is a = 4.

Not sure why it is 3a2- if you mean 3*a*2, then: 3*a*2=6a (6a-2a)+5-2(a (or a2)+a)=1 4a+5-(2a+a)=1 4a+5-2a-a=1 Then take the 5 over (remember, the +5 become -5 when transposed): 4a-2a-a=1-5 Solving the equations on both sides gives: a=-4 Is this your answer?

5 + (-3) + (-5) = -3

-1

7

3 plus 4 is 7, not 5.

10a + 15 = 5 (2a + 3)

(2a - 1)(a - 5)